Farmacoepidemiologia no Brasil: uma revisão bibliográfica - Costa, Thaisa Nayara Bezerra Gois da (2017)
Medicines consist of an important therapeutic tool of numerous diseases and is related to the generation of quality of life of the patient. The present study aims to describe the current scenario of pharmacoepidemiological research conducted in Brazil. The research is a systematic review of the Medline / PubMed, Lilacs and SciELO databases, which involved the evolution of research in pharmacoeconomics, pharmacovigilance and study of the use of drugs in Brazil in relation to the international scenario between the years from 2001 to 2016. Out of 7,042 international and national publications, 281 (3.99%) were made in Brazil, of which 111 articles were selected, according to quality and repetition criteria. The publications were distributed unevenly among the Brazilian states and regions, with the state of São Paulo and the southeast region being the most prevalent, 36.94% and 62.16%, respectively. The population of pregnant, hypertensive and oncotic patients were the most cited risk groups (19.05%) each. The most commonly reported pharmacological groups were antimicrobials (18.37%). The most discussed themes were: cost of health care (44%), within the context of pharmacoeconomics; adverse reactions (17.77%), against the context of pharmacovigilance and prescription of drugs (18.48%), regarding the use of drugs. In Brazil, despite the advances in pharmacoepidemiological legislation and gradual improvement in the inspection process, there are still deficiencies in the homogeneous distribution among Brazilian states of records, notifications, control and punishments of possible irregularities in the development and commercialization of medicines. However, it should be noted that the efficiency and success of pharmacoepidemiological processes depends not only on the competent governmental bodies, but also on notifications from health professionals, service users and suppliers.